2015
DOI: 10.1309/lmzjju6bc86wudhw
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of High Oxidative Activity in Patients With Adenomatous Intestinal Polyps and Colorectal Adenocarcinoma: Myeloperoxidase and Oxidized Low-Density Lipoprotein in Serum as New Markers of Oxidative Stress in Colorectal Cancer

Abstract: The oxidation process, which can cause mutations leading to CRC, begins development in the polyp stage. This process may be detected early by monitoring serum markers such as MPO and oxLDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Beta carotene, a pro-vitamin A carotenoid deficiency not only favors polyp dysplasia leading to CRC development but also associated with poor absorption of vitamin E, resulting in its deficiency leading to oxidative insult causing upregulated intracellular signaling which mediates tumor growth (23, 24). Vitamin C plays a key role in the production of collagen and its deficit upsets the integrity of intracellular matrix and promotes tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Beta carotene, a pro-vitamin A carotenoid deficiency not only favors polyp dysplasia leading to CRC development but also associated with poor absorption of vitamin E, resulting in its deficiency leading to oxidative insult causing upregulated intracellular signaling which mediates tumor growth (23, 24). Vitamin C plays a key role in the production of collagen and its deficit upsets the integrity of intracellular matrix and promotes tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…All the changes can be caused by oxidative stress, such as cancer suppressor [23], cell normal functions [24], special responses for pathogens [25], maximal actions, and antigen presentation [26] (Figure 6). Pathway analysis revealed that, in intestinal mucosa tissues of participants from high altitude, many pathway genes had aberrant expression and may be also related with oxidative stress, especially in inflammatory bowel diseases [27, 28], myeloperoxidase [29], ROS production [10], apoptotic cell death [30], tissue damage [31], interleukin-1 [32], oxidative modification [33], cystic fibrosis [34], natural killer cells activity [35], lymphocytes [36], fibrinolysis [37] and so on (Figure 7). …”
Section: Resultsmentioning
confidence: 99%
“…Since prototypical swarming bacteria (e.g., Proteus mirabilis, Pseudomonas aeruginosa) are associated with virulence (7,14), we surmised that bacterial swarming might be 65 well represented in colonoscopy samples and feces from humans with bacterial virulence associated pathologies (e.g., intestinal inflammation) (15). Colonoscopy aspirates were obtained from individuals with an active illness (inflammatory bowel disease -Crohn's and ulcerative colitis and other common forms of intestinal stress like intestinal polyps (16,17) as well as age and gender matched controls (those without a clinically active illness). Within our sampling pool, bacterial 70 collective spreading on soft agar was over-represented in cases with overt or clinically active intestinal stress ( Fig.…”
Section: Main Textmentioning
confidence: 99%